Risk management application in a Baja SAE team - Breno Ferreira Barrados Chorro; Alexandre Cupolillo Severino; Larissa Stéfany Leal de Alcântara; Pedro Henrique Soares da Fonseca; Luiz Gustavo Monteiro Guimarães; Júlio César Costa Campos; Antonio Marcos de Oliveira Siqueira; José Antônio da Silva; Flavio Neves Teixeira (The Journal of Engineering and Exact Sciences)
Management techniques can be beneficial for projects and it can optimize human, financial and time resources if applied to adapt to their contexts. Risk management is essential for good budget planning, given the remarkable need to prevent possible eventualities that may arise and deviate the project from its objective. Due to financial difficulties that hindered its development, the Komiketo Baja UFSJ team noticed the necessity to plan that would manage unforeseen events, since the planned budget was lesser than the actual expenditure, creating a lack of cash and preventing the purchase of essential materials for the team. This study presents the application of risk management in the team during the period 2019-2020, based mainly on the book PMBOK. In addition, it will discuss concepts such as identification, qualitative analysis, quantitative analysis, action plans, control and monitoring. Through this study, it is possible to compare before and after application, which resulted in a decrease of 128% (2018-19) to 7% (2019-20) of the difference between the amount spent and the planned amount. Several recommendations were obtained for the team's future and similar applications.